Analysis Of Errors In Limits Of Trigonometric Functions Among Students at King Saud University - Kandeel, Refat Abdelsamsd Abouelgheat (Advances in Social Sciences Research Journal, 2017)
The purpose of this study is to investigate the common errors in limits of trigonometric functions among the students at King Saud University, through analysis student responses at the items of the test, and to identify the varieties of the common errors and ratios of common errors that occurred in limits of trigonometric functions. The researcher prepared the open-ended test which consisted of (11) items about solving limits of trigonometric functions. The results showed there were a set of common errors in students’ answers, the first common error was remembering mathematical rules, laws and theories associated with the limits of trigonometric functions, the next error was mathematical procedures conducted by the students while solving questions, then the conceptual and arithmetic errors, but by less than 20%. Common errors have been determined accurately in each question of the test, as well as the number of students who made each error and the percentage of them. Keywords: Limits, trigonometric functions, common errors.